Kala-azar in Children: A Retrospective Study - Bari, MI; Talukdar, MQK; Nazir, FH; Siddiqui, AB; Haidary, MH (TAJ: Journal of Teachers Association, 2009)
Fifty children with Kala-azar 27 male (54%) and 23 female (46%) aged between 2-12 yrs, were studied retrospectively in the pediatric unit of Rajshahi Medical College Hospital to find out the optimal treatment of Kala-azar in children. Sodium stibogluconate was given intravenously at a dose of 10 mg/kbw/day for 20 days in one group (Group-A), 15 mg/kbw/day for 20 days in another group (Group-B), 10 mg/kbw/day B.D. for 20 days in another group (Group-C), and 20 mg/kg of body wt/day for 40 days is last group (Group-D). The apparent cure rates of all regimens were 100%. Side effects of sodium stibogluconate were mild, however, myocarditis developed on 37th day of treatment in one patient which reversed to normal after discontinuation of the drug. 27 patients (54%) could be followed up to six months after discharge from hospital. Two patients in group-A relapsed and none relapsed from group B, C or D. Follow-up of patients in group B, C and D showed improvement in general condition, increase in body weight, Hb% and regression of the size of the liver and spleen and ultimate rate of cure in B, C, D regimens were 100%. But ultimate cure rate in-group A was 71.4% and the significance of difference between A and other regimens (P<0.10) were statistically significant. Sodium stibogluconate 15mg/kg body weight once daily for 20 days (Group-B) had the best of cure rate with low toxicity and may be recommended for routine treatment of childhood Kala-azar in this country. doi: 10.3329/taj.v17i2.3455 TAJ 2004; 17(2): 99-103